Drink beer to save the planet - Lauren Barfield; Chris Mallate; Rachel Boyle; Laurelle Metusela; Barnaby Bartlett (Australasian Accounting, Business and Finance Journal, 2009)
This student poster display example considers the ethics of the marketing of the “Cascade Green” beer in Australia. Issues considered include the ethics of marketing beer, the environmental impacts of the beers marketing and packaging and a reflection upon the societal impacts of the product.